Memórias e sentidos de natureza nas práticas educativas da comunidade Quilombola Castainho/PE - Mélo, Cláudia Fernanda Teixeira de (2018)
Throughout the history of mankind, some changes have occurred in relation to the idea of nature, which have been inserted into philosophical, sociological, educational and environmental debates, which have evolved in the mode of production, cultural traits, technology, educational processes and construction of knowledge. Thus, certain educational processes occurring in institutions such as: school, church, associations, municipal councils, political leaderships and social representations that articulate, connect internalize knowledge in social construction and cultural valuation. These are inherited through cultural development and knowledge about nature, since they demonstrate how these educational processes give their subjects an experience, appropriation, belonging, autonomy in the production of knowledge about their identities and their cultural territories. The present thesis aimed to analyze the meanings attributed by subjects of the rural community Castainho through its educational processes. The research had a bibliographic study plan, distributed in stages of documentary apparatus, under the ethnographic method, through oral history, based on the oral history in locus, together with the members of the centennial Quilombola community of Agreste Meridional de Pernambuco. Oral history and memory guided the process of organizing data on daily experience and practice (plural and routine activities) of subjects in this rural community, mixing past and present, anchored in orality to retrieve information from the locality based on narratives on their social place and their relations with nature to evidence the senses of nature attributed by the community within a "memorial ethnography" that were used with the participants on the conservation of the environment and the educational processes. In this sense, the research contributed to the systematization of the knowledge about the memories and the senses of nature by expanding studies of the identity and socio-cultural processes as a conservation action of the place, as well as in the reflection of the man's belonging to nature through socio-cultural identity processes of a place, by conserving the environment (nature) through educational processes.